2015
DOI: 10.1097/ico.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Review of Different Bubble Types Formed During Pneumodissection (Big-Bubble) Deep Anterior Lamellar Keratoplasty

Abstract: The type 2 bubble is more likely to form in elderly patients and those with deep corneal scars and thin corneas. Because of the high rate of conversion to penetrating keratoplasty, better surgical strategies may be needed to manage type 2 bubbles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…15 In our study, postoperative complications are reported more frequently after PK compared to DALK and it is comparable to 31.8% vs. 4.5% in another study. 16 This may be because DALK is essentially an extraocular procedure so there are less chances of complications in DALK as compared to PK.…”
supporting
confidence: 68%
“…15 In our study, postoperative complications are reported more frequently after PK compared to DALK and it is comparable to 31.8% vs. 4.5% in another study. 16 This may be because DALK is essentially an extraocular procedure so there are less chances of complications in DALK as compared to PK.…”
supporting
confidence: 68%
“…It is more prone to form in old patients and those with deep corneal scars, advanced keratoconus, and thin corneas. 11 In one study, eyes with the type 2 bubble showed a high frequency of conversion to PK (86%). 11 Because of this, it is imperative that the surgeon is able to recognize intraoperatively which BB has formed and better surgical strategies adopted to manage type 2 bubbles for successful DALK.…”
Section: Discussionmentioning
confidence: 97%
“…16,28,29 Our study instead chose to look at BB type based on size, with full BB describing a single, centrally located bubble of 7 mm in diameter or larger, partial BB describing a single bubble smaller than 7 mm in diameter or multiple smaller bubbles, and no BB describing the complete absence of any bubble. We did this because clinically, our distinction of full, partial, or no BB formation determines the next step of the DALK procedure.…”
Section: Discussionmentioning
confidence: 99%